Formal External Financing in Transition Economies - An Empirical Study with Focus on Public Ownership - Novovic Engstrand,Sara; Lundström,Johanna (2007)
Economic theory states that public firms are less creditworthy due to lower efficiency, and hence are expected to use less formal financing than private firms. In communist countries however, all formal capital was distributed the favored public firms and despite various market-oriented reforms in the transition economies of today, these old structures are expected to linger. Therefore formal credit in transition economies is still likely to be distributed to public firms regardless of their creditworthiness, even though vast differences between the economies are expected, as some are almost fully comparable to developed countries, while others among the world’s least developed countries. The empirical investigation in this thesis is conducted through a binary choice model. The transition economies are divided into three groups depending on their degree of financial and market-oriented reforms. The aim is to discern whether there is a difference in firms’ usage of formal external credit depending on degree of reforms on the one hand and to examine differences between public and private firms’ usage on the other. The results show that firms in all transition economies experience very similar probabilities of using formal credit, regardless of the degree of reforms. However, a closer look at the composition of firms using formal capital, shows that there indeed are great differences between the countries. Public firms receive significantly less formal external capital than private firms in the most reformed economies. In the middle reformed economies the difference between public and private firms is smaller, and in the least reformed transition economies the ownership variable did not have any significant impact on firms’ use of formal credit. We conclude that the differing degree of financial and market-oriented reforms do not affect the overall use of formal credit, but is reflected in the distribution of credit, which is more market-based in economies that have reached a higher degree of transition.
Keywords: regression analysis; Transition Economy; Formal Financing; Public Enterprise; Economics, econometrics, economic theory, economic systems, economic policy; Nationalekonomi, ekonometri, ekonomisk teori, ekonomiska system, ekonomisk politik